INOVASI KULINER LOKAL: TAHU DAN TEMPE NAIK KELAS DI ERA MODERN (Program Studi Pendidikan Pancasila dan Kewarganegaraan) - Nourel Islamay Diandra; Laila Fatia Maharani; Perina Dwi Astuti; Karyadi Hidayat (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
Abstrak: This study aims to analyze the ingredients tardisional yaigu tempeh and tofu in order to compete in the modern market and become a food Class. In addition to the nutritional content of tempeh and tofu that is not less than the nutritional content of animals, tempeh and tofu can compete with processed foods made from chicken and tofu. At this time, tofu and tempeh are transformed into high class foods, namely dismum tofu and tempeh sticks that are similar to chicken cordon bleu. By using descriptive methods, this article explores how innovations from traditional local culinary, tofu and tempeh into high-class foods that are in demand by many people and how marketing suoaya have high competitiveness with animal-based foods such as chicken and beefAbstrak: This study aims to analyze the ingredients tardisional yaigu tempeh and tofu in order to compete in the modern market and become a food Class. In addition to the nutritional content of tempeh and tofu that is not less than the nutritional content of animals, tempeh and tofu can compete with processed foods made from chicken and tofu. At this time, tofu and tempeh are transformed into high class foods, namely dismum tofu and tempeh sticks that are similar to chicken cordon bleu. By using descriptive methods, this article explores how innovations from traditional local culinary, tofu and tempeh into high-class foods that are in demand by many people and how marketing suoaya have high competitiveness with animal-based foods such as chicken and beef